Effect of annealing on the defect-mediated blue phosphorescence in ZnO nanocrystals. Issue 1 (23rd December 2020) - Das, Sagnik; Ghorai, Uttam Kumar; Dey, Rajib; Ghosh, Chandan Kumar; Pal, Mrinal
Abstract : We observed and analyzed the effect of thermal annealing on the point defect concentration and in turn on the defect mediated blue phosphorescence in nanocrystalline ZnO. Abstract : Recently, UV/NUV excitable RGB phosphors with precisely tunable PL emission properties have been in high demand for their suitability in the fabrication of white LEDs. In this paper, we report to have tuned the PL intensity, shade, and color temperature of the defect-mediated blue phosphorescence of ZnO nanopowders by systematic annealing at different temperatures. The ZnO nanopowder was prepared by a facile and cost-effective aqueous solution-precipitation method. The as-synthesized nanopowder was annealed at different temperatures ranging from 150 °C to 850 °C and all these samples were characterized by XRD, FESEM, EDX, BET, Raman spectroscopy, and UV-Vis spectroscopy to have insight into their microstructural, compositional, and band-structure details. Optical studies of the samples were conducted by PL and τ-PL spectroscopy. Color coordinates of the samples were obtained from the CIE plots derived from the PL spectra. The CIE coordinates were further used to calculate the CCT values of the samples. τ-PL spectroscopy was carried out to measure the life-time of the photogenerated electrons. PL studies of the samples revealed that the blue emissions have red, yellow, and blue components originating from crystalline point defects, viz. zinc interstitial (Zni ), and oxygen interstitial (Oi ). Annealing at different temperatures triggered changes in the defect concentrations leading to the corresponding changes in the intensity, shade, and color temperature of the blue phosphorescence.